THE ROLE OF CONTENT AND LANGUAGE INTEGRATED LEARNING (CLIL) IN THE TRAINING OF FUTURE ENGLISH LANGUAGE TEACHERS - Mannonova Bahoroy Ibodulla qizi,; Abdullayeva Lola Tohirovna, (MULTIDISCIPLINARY JOURNAL: FUNDAMENTAL RESEARCH SCIENTIFIC JOURNAL, 2026)
This article examines the role and significance of Content and Language Integrated Learning (CLIL) in the training of future English language teachers. The study analyzes the theoretical foundations of CLIL, its pedagogical potential, and its impact on the development of professional competencies. It highlights how integrating subject content with language learning enhances students’ communicative abilities, critical thinking, and cognitive skills. The article also discusses the practical implementation of CLIL in teacher education, as well as its advantages and challenges. The findings suggest that CLIL is an effective and innovative approach that can improve the quality of teacher training and contribute to the development of highly qualified English language teachers.